2020
DOI: 10.18388/abp.2020_2898
|View full text |Cite
|
Sign up to set email alerts
|

Roundup-induced biochemical and histopathological changes in the liver and kidney of rats: the ameliorative effects of Linum usitatissimum oil

Abstract: The present study was undertaken to evaluate the protective effects of Linum usitatissimum oil (LuO) against sub-chronic Roundup (RDP)-induced toxicity and oxidative stress in rats. Rats were divided into four groups: control group (no treatment), RDP group (Roundup at 269.9 mg/kg b.w.), LuO group (0.5 g/kg b.w. of LuO) and RDP+LuO group (RDP and LuO simultaneously). LuO decreased the ferric reducing antioxidant power (FRAP) (IC50=10.36 μg/ml) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) (IC50=22.85 mg/ml) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 69 publications
5
13
0
Order By: Relevance
“…The hypertriglyceridemia and high HDL may be attributed to increase in the lipid rate of peroxidation and free radical release. These findings corroborate similar studies by Djaber et al, 2020 , El-Shenawy, 2009 . Again, the findings from the current study showed that cyanocobalamin treatment before or after GBH exposure was effective in stabilizing the cholesterol levels in the blood.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The hypertriglyceridemia and high HDL may be attributed to increase in the lipid rate of peroxidation and free radical release. These findings corroborate similar studies by Djaber et al, 2020 , El-Shenawy, 2009 . Again, the findings from the current study showed that cyanocobalamin treatment before or after GBH exposure was effective in stabilizing the cholesterol levels in the blood.…”
Section: Discussionsupporting
confidence: 93%
“…Glyphosate-based herbicides (GBHs) are among the economically important agrochemicals widely used. Glyphosate, chemically referred to as N-phosphonomethyl glycine is the active ingredient in GBHs, which include formulations such as Roundup ( Djaber et al, 2020 , Panzacchi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ameliorative effects on roundup-induced biochemical and histopathological changes in the liver and kidney of rats 0.5 g/kg of body weight [109] Morus alba L.…”
Section: Essential Oil Ratsmentioning
confidence: 99%
“…According to our results obtained after treatment of rats for 3 months, oral administration of decocted FG, geniposide, and genipin detrimentally effected the body weight of rats and caused the liver and kidneys to swell over time. AST, ALT, and ALP are typical indicators of liver function, while CRE and BUN are indicative of kidney function (Djaber et al., 2020; Kamel et al., 2020). When renal function is impaired, serum CRE will increase obviously (Wang et al., 2010), and BUN will be discharged through glomerular filtration (Suzuki et al., 2019).…”
Section: Discussionmentioning
confidence: 99%